Upaya Inovatif Menuju Pesantren Bebas Skabies di Pesantren Ar Roshifah Tasikmalaya: Innovative Efforts Towards Scabies-Free Islamic Boarding Schools at Ar Roshifah Tasikmalaya Islamic Boarding School - Triyani, Yani; Hikmawati, Deis; Andarini, Mia Yasmina; Rahmawati, Irma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The incidence of scabies and factors of clean and healthy living behavior (PHBS) in Islamic boarding schools are still a problem. Therefore, community service activities (PKM) try an innovative approach with assistance in increasing the PHBS of students and pesantren administrators using the problem-based learning (PBL) method at the Ar Roshifah Islamic boarding school, Leuwisari sub-district, and Tasikmalaya district are expected to find a solution. In stage 1 of the PKM activity, physical examination of all of the administrators and students, most types of diseases are found, which are then used as a topic of discussion in stage 2—introducing clean and healthy living behaviors with the (PBL) method. This method uses problems as learning stimuli. There is group work for interaction (students and teachers are divided into small groups of 10-12 people) and the PKM team as tutors and facilitators. In conclusion, at the end of the activity, the students and administrators learn about scabies, starting from the etiology, risk factors, symptoms, methods of treatment, and prevention independently. They find out until they understand the roots of existing health problems and are expected to have an impact on daily life towards personal health and the environment to avoid scabies.